Krótkie formy liryczne wobec problemów przedstawiania rzeczywistości - Telicki, Marcin (Wydawnictwo Naukowe UAM, 2006)
An expression "the shortest poem" as a genre term seems to be imprecise, however, both its functioning amongst other literary forms and unstabilised boundaries of the modern genology make it that it is a necessary definition. Outstanding modern poets (Białoszewski, Miłosz, Grochowiak and others), reach for this undefined attractive form, trying to make it a key to the world (hence the problems of mimesis which are discussed in this article) and to the other world (category of transgression). What is more "the shortest poems" appear most often in their later work, and minimalisation of the form leads to condensation of meanings (like a sage, they utter fewer words, but important ones). The article is also a point of departure for the discussion on the state of modern culture and condition of man who continuously faces the same fundamental questions.
Short lyrical forms in view of presentation of problems of reality